Fungicide resistance of Botrytis cinerea from strawberry to procymidone and zoxamide in Hubei, China - Muhammad Adnan; Mohamed Sobhy Hamada; Matthias Hahn; Guo-Qing Li; Chao-Xi Luo (Phytopathology Research, 2019)
Abstract Gray mold, caused by Botrytis cinerea, is one of the most destructive diseases of strawberry in China. For resistance monitoring, 198 B. cinerea isolates were collected from strawberry greenhouses at 10 locations in Hubei Province. The isolates were screened for resistance to fungicides procymidone and zoxamide. In mycelium growth assays for procymidone, the mean values of effective concentration at which mycelium growth is inhibited by 50% (EC50) for sensitive (ProS) and resistant (ProR) isolates were 0.25 μg/mL and 2.21 μg/mL, respectively. The frequency of ProR isolates was 14%, and the highest frequency (48%) was observed in Yichang. Positive cross-resistance was detected for ProR isolates to other dicarboximide fungicides, but not to phenylpyrroles. Comparative analysis of fitness parameters revealed increased osmotic sensitivity of ProR isolates compared to ProS ones. Sequence analysis of the dicarboximide target gene BcOs1 revealed that ProR isolates carried either a single point mutation at codon 365 (I365S) or a pair of point mutations (Q369P and N373S). The mean EC50 values for zoxamide sensitive (ZoxS) and resistant (ZoxR) isolates were 0.31 μg/mL and 7.76 μg/mL, respectively. Only six (3%) isolates from three locations were found to be resistant to zoxamide. All ZoxR isolates were found resistant to carbendazim. Fitness parameters did not show significant difference between ZoxR and ZoxS isolates. Sequence analysis of the beta-tubulin gene in resistant isolates revealed four previously reported point mutations (E198A, E198K, F200Y and T351I). The mutation T351I was detected only in the isolates possessing E198K point mutation. Mutation F200Y was detected in a highly resistant isolate. Results of this study will be helpful for the management of fungicide resistance in B. cinerea.